FORMULASI GELHAND SANITIZER DARI KITOSAN DENGAN BASIS NATRIUM KARBOKSIMETILSELULOSA - Supomo Supomo; Yullia Sukawati; Fredi Basyar (Jurnal Ilmiah Manuntung, 2015)
Chitosan has been widely used in industrial, food, pharmaceuticals and agriculture. Chitosan is a natural biocompatible polymers means that as nature does not have the side effect, non-toxic, can not be easily digested and broken down by microbes (biodegradable). This study aims to determine whether the chitosan may be formulated into dosage gel hand sanitizer that meets the requirements of the physical stability of the gel.Chitosan is formulated with 3 varying concentrations of Na CMC basis of 3%, 4.5% and 6%. Tests conducted gel formulation is the physical stability test which includes organoleptic test, homogeneity, pH test, test dispersive power, viscosity test and test consistency. Testing is done every week for 4 weeks of storage.Results of testing physical properties of chitosan gel hand sanitizer has the shape and color stable but the resulting aroma change during storage. pH gel meet the requirements, the consistency test of phase separation does not occur, the homogeneity test showed no homogeneous gel, gel dispersive power does not meet the requirements, the viscosity of the gel preparation third formula does not meet the requirements of viscosity gel